The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
Sixth IEEE International Conference on Advanced Learning Technologies (ICALT'06) 2006
DOI: 10.1109/icalt.2006.1652633
|View full text |Cite
|
Sign up to set email alerts
|

Virtually Collaborating Across Cultures: A Case Study of an Online Theatrical Performance in a 3DCVE Spanning Three Continents

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Three-dimensional virtual spaces provide a more vivid and realistic environment compared to 2D representations, and facilitate the creation of a more correct and complete mental model of a collaborative task at hand (Chittaro & Serra, 2004). In line with this assumption, Wyeld et al (2006) found that the 3D aspect led to more active social involvement and concretization of the performed activities in an intercultural collaboration task in a virtual world.…”
Section: Virtual Space and Place Metaphorsmentioning
confidence: 69%
See 4 more Smart Citations
“…Three-dimensional virtual spaces provide a more vivid and realistic environment compared to 2D representations, and facilitate the creation of a more correct and complete mental model of a collaborative task at hand (Chittaro & Serra, 2004). In line with this assumption, Wyeld et al (2006) found that the 3D aspect led to more active social involvement and concretization of the performed activities in an intercultural collaboration task in a virtual world.…”
Section: Virtual Space and Place Metaphorsmentioning
confidence: 69%
“…The use of avatars as a virtual representation of interacting individuals has been claimed to be of great pedagogical value. Wyeld et al (2006) found that students across all cultures rated the notion of being able to ''hide'' behind their avatar as a ''liberating and empowering'' experience, especially for those who may not have ''spoken out'' in a cross-cultural FTF encounter. Moreover, virtual worlds provide its users with the freedom of defining their virtual appearance and identity.…”
Section: Avatar Appearance and Identity Tourismmentioning
confidence: 99%
See 3 more Smart Citations